MENINGKATKAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN COOPERATIF LISTENING TEAM PADA MATA PELAJARAN BAHASA INDONESIA DI KELAS V SDN 244 PALEMBANG - Gustian Rifaldi; Yenny Anwar; Inda Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research was conducted to improve students' learning outcomes in Indonesian language learning by using the Cooperative Listening Team learning model. The research method uses a class action research design consisting of two cycles, where one cycle consists of 1 meeting. The stages of each cycle consist of four stages, namely planning, implementation, observation, and reflection. The subjects in this study were fifth grade students of SDN 244 Palembang, totaling 25 students, consisting of 11 male students and 14 female students. Data collection techniques used observation techniques, student learning outcomes tests, and interviews. This study shows that the learning outcomes of students in the pre-cycle get an average score of 60.22 then increase from 70.87 in cycle I to 78.70 in cycle II. The percentage of completeness has increased from 40% in the pre-cycle, then to 64% in cycle I and increased to 76% in cycle II. Therefore, it can be concluded that the results of the study show that the use of the Cooperative Listening Team learning model can improve the learning outcomes of grade V students of SDN 244 Palembang.